From Reach to Active Consumers: Effective Social Media Marketing Strategies at Popsio.id - Putu Diana Karisma Putri; A.A.N. Oka Suryadinatha Gorda (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study explores the effectiveness of social media strategies, specifically TikTok Live Shopping, in converting reach into active and loyal consumers at Popsio.id, a local fashion brand from Bali specializing in women's bags. The research employs a qualitative case study approach, combining in-depth interviews with brand owners, social media managers, TikTok observers, and consumers, as well as observation and documentation of Popsio.id's digital activities. The study highlights how Popsio.id leverages Instagram as a visual catalog, Shopee as a primary marketplace, and TikTok for interactive engagement and real-time sales. The findings reveal that consistent and entertaining content, particularly during TikTok live sessions, significantly influences consumer engagement and purchasing decisions. Furthermore, soft-selling techniques and trend-sensitive content contribute to avoiding consumer resistance and increasing brand visibility. Despite successfully expanding its reach, Popsio.id still faces challenges in building long-term customer loyalty and ensuring product expectations align with online content. This research contributes to digital marketing theory by applying the hierarchy of effects model and suggesting practical strategies for local brands seeking to increase customer conversion through interactive social platforms. These insights can serve as a reference for other MSMEs aiming to optimize social media as a sales and branding channel.